Redefining the technique for the radiologic measurement of slip in spondylolisthesis - Bourassa-Moreau, Etienne; Mac-Thiong, Jean-Marc; Labelle, Hubert (Spine (Philadelphia, Pa. 1976), 2010)
Comparison of 2 radiographic measurement techniques of slip severity in spondylolisthesis. To analyze the differences between 2 radiologic measurement techniques of slip severity in L5-S1 developmental spondylolisthesis. Different techniques for the assessment of slip in spondylolisthesis have been described in the literature, resulting in 2 different methods to report the position of the L5 vertebra on the S1 superior endplate. The clinical impact of these differences in slip measurement is unknown. Radiographs of 130 subjects with developmental spondylolisthesis were reviewed. Two different techniques were used to assess the grade and percentage of slip. The technique 1 uses a line drawn from the L5 vertebra postero-inferior corner that is perpendicular to the S1 vertebra endplate. The technique 2 uses a line tangential to the L5 vertebra posterior wall that intersects the S1 vertebra endplate. The lumbosacral angle (LSA) was also measured to assess the orientation of L5 over S1. The slip percentage and grade obtained from the 2 techniques were compared. The influence of the LSA on the measurement of slip severity was also assessed. A significant difference (P < 10(-5)) was found between technique 1 (mean = 34.2% +/- 32.6%) and technique 2 (mean = 42.5% +/- 25.8%) with respect to the slip percentage. Eight subjects were found to switch classification from a low to a high-grade slip (or inversely) depending on the technique used. There was a significant relationship between the LSA and the difference in the measurement of slip percentage using either technique 1 or technique 2. The 2 measurement techniques can have a significant impact on the interpretation of slip severity in spondylolisthesis. The differences between the measurement techniques are influenced by the orientation of L5 over S1 and could potentially affect the clinical decision making. It is important to standardize and specify the technique used to plan and assess interventions in L5-S1 developmental spondylolisthesis.